Phase Swapping Load Balancing Algorithms, Comprehensive Survey - Al-Kharsan, Ibrahim H.; Marhoon, Ali. F.; Mahmood, Jawad Radhi (Iraqi Journal for Electrical and Electronic Engineering, 2019)
The power quality nowadays of the low voltage distribution system is vital for the utility and the consumer at the same time. One disturbing issue affected the quality conditions in the radial distribution system is load balancing. This survey paper is looking most the articles that deal with the phase nodal and lateral phase swapping because it is the efficient and direct method to maintain the current and voltage in balance situation, lead to a suitable reduction in the losses and preventing the wrong tripping of the protective relays.